A tri-modal tissue-equivalent anthropomorphic phantom for PET, CT and multi-parametric MRI radiomics. (June 2022) - Gallivanone, Francesca; D'Ambrosio, Daniela; Carne, Irene; D'Arcangelo, Micol; Montagna, Paolo; Giroletti, Elio; Poggi, Paolo; Vellani, Cecilia; Moro, Luca; Castiglioni, Isabella
Highlights: Use of agar-based gel mixtures as tissue-equivalent materials for phantoms. Use of agar-based gel mixtures to simulate simultaneously PET, CT and MRI signal. Use of agar-based gel mixtures to customize phantom for translational studies. Multimodal imaging phantom overcomes hybrid systems issues in radiomics methodology. Abstract: Purpose: Radiomics has emerged as an advanced image processing methodology to define quantitative imaging biomarkers for prognosis and prediction of treatment response and outcome. The development of quantitative imaging biomarkers requires careful analysis to define their accuracy, stability and reproducibility through phantom measurements. Few efforts were devoted to develop realistic anthropomorphic phantoms. In this work, we developed a multimodality image phantom suitable for PET, CT and multiparametric MRI imaging. Methods: A tissue-equivalent gel-based mixture was designed and tested for compatibility with different imaging modalities. Calibration measurements allowed to assess gel composition to simulate PET, CT and MRI contrasts of oncological lesions. The characterized gel mixture was used to create realistic synthetic lesions (e.g. lesions with irregular shape and non-uniform image contrast), to be inserted in a standard anthropomorphic phantom. In order to show phantom usefulness, issues related to accuracy, stability and reproducibility of radiomic biomarkers were addressed as proofs-of-concept. Results: The procedure for gel preparation was straightforward and the characterized gel mixture allowed to mime simultaneously oncological lesion contrast in CT, PET and MRI imaging. Proofs-of-concept studies suggested that phantom measurements can be customized for specific clinical situations and radiomic protocols. Conclusions: We developed a strategy to manufacture an anthropomorphic, tissue-equivalent, multimodal phantom to be customized on specific radiomics protocols, for addressing specific methodological issues both in mono and multicentric studies.